2001
DOI: 10.1091/mbc.12.9.2590
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Cell-type–specific Genes inDictyostelium

Abstract: Cell-type specific genes were recognized by interrogating microarrays carrying Dictyostelium gene fragments with probes prepared from fractions enriched in prestalk and prespore cells. Cell-type specific accumulation of mRNA from 17 newly identified genes was confirmed by Northern analyses. DNA microarrays carrying 690 targets were used to determine expression profiles during development. The profiles were fit to a biologically based kinetic equation to extract the times of transcription onset and cessation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…Overexpression of gadB-gfp in gadA Ϫ /gadB Ϫ cells also showed a similar extracellular GABA level when compared with gadB-gfp overexpression in WT cells, suggesting GadB is the main functioning glutamate decarboxylase during this period. Disruption of gadA showed statistically indistinguishable extracellular GABA levels as compared with control cells, which correlated with previous results that gadA is transcribed at basal levels during growth and early development (15). Interestingly, overexpression of untagged or tagged gadA in WT cells significantly decreased extracellular GABA level to 16 M, and overexpression of gadA-gfp in gadA Ϫ /gadB Ϫ cells exhibited an even lower extracellular GABA level of 8 M.…”
Section: A Gaba B Receptor-like Protein Grlb Is Involved In Earlysupporting
confidence: 89%
See 2 more Smart Citations
“…Overexpression of gadB-gfp in gadA Ϫ /gadB Ϫ cells also showed a similar extracellular GABA level when compared with gadB-gfp overexpression in WT cells, suggesting GadB is the main functioning glutamate decarboxylase during this period. Disruption of gadA showed statistically indistinguishable extracellular GABA levels as compared with control cells, which correlated with previous results that gadA is transcribed at basal levels during growth and early development (15). Interestingly, overexpression of untagged or tagged gadA in WT cells significantly decreased extracellular GABA level to 16 M, and overexpression of gadA-gfp in gadA Ϫ /gadB Ϫ cells exhibited an even lower extracellular GABA level of 8 M.…”
Section: A Gaba B Receptor-like Protein Grlb Is Involved In Earlysupporting
confidence: 89%
“…On the basis of weak activity of GadA, it can be inferred that only a small amount of GABA is required for spore formation. It has been shown that GadA expression is enriched in pre-spore cells and GABA generated from prespore cells can induce sporulation (15,21). 1 nM GABA is sufficient to maximally induce spore formation (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be important to determine whether the late mitotic events and G1-phase arrest are required for spore cell differentiation or stalk formation. Certainly, prespore-specific genes and genes that become prespore enriched are expressed in some cells well before mitosis begins so it is unlikely that G1 arrest is required for all aspects of prespore differentiation (Fosnaugh and Loomis, 1993;Good et al, 2003;Haberstroh and Firtel, 1990;Iranfar et al, 2001;VanDriessche et al, 2002;Williams et al, 1989). Microtubule destabilizing drugs that block mitosis do not block development suggesting that prespore cells need not divide prior to spore differentiation (Cappuccinelli and Ashworth, 1976;Cappuccinelli et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Two genes encoding the enzyme that converts glutamate to GABA, glutamate decarboxylase, can be recognized in the Dictyostelium genome. Microarray-based experiments have shown that one of these genes, gadA, is expressed only after 10 hours of development and its mRNA accumulates to a peak at 18 hours when the cells are initiating fruiting body formation (Iranfar et al, 2001). The other gene, gadB, is expressed in growing cells and its mRNA continuously decreases during development (Van Driessch et al, 2002;Iranfar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%